OP14 Consumers, retailers and policymakers' perspectives on policy options in retail settings to improve diet – a qualitative systematic review. (26th August 2022) - Dhuria, Preeti; Barrett, Millie; Lawrence, Wendy; Roe, Emma; Baird, Janis; Vogel, Christina
Abstract : Background: In July 2021, the UK government announced the introduction of Food (promotions and placement) legislation from October 2022 aiming to create healthier food environments. In some countries, policies to support healthy eating have not been perceived as effective and this has led to policy withdrawal. Exploring stakeholder perspectives on previous policies can provide insights into factors influencing acceptability, implementation and adoption of the policy. This study synthesised the views of consumers, retailers and policymakers on previous policies to improve diet by conducting a systematic qualitative literature review to inform future nutrition policy implementation. Methods: Five scientific literature databases were searched for qualitative studies published from 1996 to January 2021. Studies focusing on policies to improve food retail environments and conducted with adults over 18 years in high income countries were included. Study quality was assessed with the Critical Appraisal Skills Programme (CASP) tool. Two researchers completed screening of full-text papers, data extraction and analysis. Thematic synthesis was conducted in NVIVO following Thomas and Harden's approach. Results: Twenty-one studies, mostly from the USA and Australia, met the inclusion criteria. The cross-cutting themes identified across all stakeholder groups included the need for i) clear policy scope and definitions, ii) establishing stakeholder support, and iii) avoiding negative financial impact. Government policies to support healthier choices were perceived positively by consumers. Retailers raised concerns about financial impacts and practical implementation considerations but were receptive to changing consumer trends. Policymakers highlighted that both political will and opportunity were essential for policy initiation. Potential factors undermining policy effectiveness included consumer shift to other unhealthy behaviours, industry tactics, and enforcement challenges. Discussion: Consumers acknowledge that current marketing strategies are manipulative and recognise the need for government policies to restrict unhealthy foods and increase the availability and marketing of healthier options. Retailers concerns relate to impact on profits and low consumer demand. They require government support for modifications in supply chains, increased revenues from healthier foods and to alter societal norms. For consistent and effective policy implementation the enforcers' needs should be assessed and supported. Government consultations and grey literature weren't included in this review. Conclusions: Findings from this review will help inform the research strategy for mapping stakeholders perspectives for the upcoming Food legislation. Ongoing examination of the contextual factors that influence policy acceptability, implementation and enforcement is required to enable this novel policy to achieve its intended effects, reduce inequalities and avoid negative unintended consequences.